2021
DOI: 10.1021/acs.jpcb.1c08073
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Localization Microscopy of 3D Orientation and Anisotropic Wobble Using a Polarized Vortex Point Spread Function

Abstract: Within condensed matter, single fluorophores are sensitive probes of their chemical environments, but it is difficult to use their limited photon budget to image precisely their positions, 3D orientations, and rotational diffusion simultaneously. We demonstrate the polarized vortex point spread function (PSF) for measuring these parameters, including characterizing the anisotropy of a molecule’s wobble, simultaneously from a single image. Even when imaging dim emitters (∼500 photons detected), the polarized vo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(88 citation statements)
references
References 74 publications
(172 reference statements)
5
63
0
Order By: Relevance
“…Moreover, each NR exhibits relatively little rotational diffusion, i.e., small wobble angle Ω, (Fig. 3(f)), which is consistent with previous characterizations of NR within planar SLBs [19,35].…”
Section: D Smolm Reveals Membrane Morphology and Compositionsupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, each NR exhibits relatively little rotational diffusion, i.e., small wobble angle Ω, (Fig. 3(f)), which is consistent with previous characterizations of NR within planar SLBs [19,35].…”
Section: D Smolm Reveals Membrane Morphology and Compositionsupporting
confidence: 90%
“…3(a), SI Section 6) [33,34] using two lipid compositions: DPPC (di(16:0) phosphatidylcholine) only vs. a mixture of DPPC and cholesterol (chol). Previous studies [19,35] have shown that NR orients itself perpendicular to the membrane when a high concentration (40% used here) of chol is present. Thus, a spherical SLB enables us to validate simultaneously orientation and position imaging performance, quantifying both precision and accuracy.…”
Section: D Smolm Reveals Membrane Morphology and Compositionmentioning
confidence: 77%
See 1 more Smart Citation
“…A hallmark of biological systems is their careful control and regulation of biomolecular interactions at the nanoscale, via mechanical forces, 1 lipid membranes, 2 and biomolecular condensates, 3,4 to name a few examples. Owing to their sensitivity and versatility, 5,6 single fluorescent molecules and their translational and rotational dynamics have been used to study a variety of biochemical processes, including the motions of molecular motors, 7,8 conformations of supercoiled DNA, [9][10][11] and the structure and organization of actin filaments, 12,13 amyloid aggregates, 14,15 and lipid membranes. 16,17 Simultaneously resolving the 3D position, 3D orientation, and rotational diffusion of single fluorophores, termed single molecule orientation localization microscopy (SMOLM), requires careful manipulation of the phase and polarization of only hundreds or thousands of photons.…”
Section: Introductionmentioning
confidence: 99%
“…Limited by challenging signal-to-background ratios (SBRs) in typical single molecule (SM) experiments, microscopists have developed various SMOLM techniques to improve measurement performance, 18 approaching the theoretical limits under ideal conditions. [19][20][21] To use precious fluorescence photons more efficiently and maximize signal-to-noise ratios (SNRs), most recently developed techniques create dipolespread functions (DSFs), or images of dipole emitters, with compact footprints 11,12,15,17,22 and thusly achieve higher precision and accuracy. One key challenge with these designs is that orientation estimation requires fitting subtle features within noisy images.…”
Section: Introductionmentioning
confidence: 99%